International cooperation for a biodiverse future: Opportunities and challenges under the Kunming-Montreal Global Biodiversity Framework - Zhijun Zhang; Dawang Cao; Teng Ma; Huirong Liu; Zhengkai Mao (Global Ecology and Conservation)
The Kunming-Montreal Global Biodiversity Framework (KM-GBF) is the latest outcome of the 15th Conference of the Parties to the Convention on Biological Diversity (CBD COP 15), marking a historic achievement in shaping the global biodiversity conservation agenda post-2020. The KM-GBF balances ambitious goals with pragmatic implementation plans, such as establishing clear timelines and mobilizing financial resources, aiming to quickly reverse the ongoing trend of global biodiversity loss. Therefore, this review aims to explore the opportunities and challenges within the international cooperation mechanism established under the KM-GBF. Through a textual analysis of the KM-GBF, the legal framework supporting its international cooperation mechanism was clarified. Moreover, building on the innovative practices that emerged from the implementation of the KM-GBF, novel concepts and approaches in international cooperation for biodiversity conservation were identified, summarized, and highlighted. Ultimately, the practical challenges encountered during the implementation process, including funding shortfalls, technology transfer barriers, and the divergence of interests between developed and developing countries, were addressed, offering recommendations to guide future policy-making and execution.